Lithium ion battery

By using nonaqueous electrolyte and specific compounds in lithium-ion batteries, the specific surface area and particle size of the negative electrode material layer are regulated to form an optimized interface film, which solves the problem of instability of the SEI layer and improves the cycle stability and performance of the battery , especially in high and low temperature conditions.

CN119153783APending Publication Date: 2024-12-17SHENZHEN CAPCHEM TECH CO LTD

Patent Information

Application Number
CN202410974787.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have challenges in cycle stability, safety and fast charging capabilities, mainly due to the instability and unevenness of the solid electrolyte interface phase (SEI) layer on the graphite negative electrode, resulting in electrochemical stability and electrode consumption problems.

Method used

Non-aqueous electrolyte, containing specific compounds and lithium salt additives, is used to regulate the specific surface area and particle size of the negative electrode material layer to form an optimized negative electrode interface film to ensure that the proportion of inorganic and organic matter components is 0.5≤Wa/Wb≤10 , optimize the lithium-ion interface transmission channel and improve the battery's high-temperature, low-temperature and rate performance.

Benefits of technology

It realizes a thinner, denser and more stable negative electrode interface mask, optimizes lithium ion interface transmission, improves the low-temperature performance, rate performance and high-temperature storage performance of the battery, and ensures the high efficiency and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153783A_ABST
    Figure CN119153783A_ABST
Patent Text Reader

Abstract

In order to solve the problem that an existing lithium ion battery is insufficient in rate performance, high-temperature performance and low-temperature performance, the invention provides a lithium ion battery which comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, the negative electrode comprises a negative electrode material layer containing a negative electrode active material and a negative electrode interface film formed on the surface of the negative electrode material layer, and the non-aqueous electrolyte is formed on the surface of the negative electrode material layer. The specific surface area of the negative electrode material layer is 0.5-5 m < 2 > / g, the median particle size of the negative electrode material layer is 8-17 [mu] m, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, the additive comprises a lithium salt type additive and a compound represented by a structural formula 1: # imgabs0, and the lithium ion battery satisfies the following condition: 0.5 < = Wa / Wb < = 10. According to the lithium ion battery provided by the invention, the proportion of the organic matter component and the inorganic matter component in the negative electrode interface film is mutually coordinated, so that a lithium ion interface transmission channel can be optimized, and the high-temperature storage performance is optimal while the low-temperature performance and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage components, and in particular relates to a lithium ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) have become the mainstream energy storage technology ubiquitous in portable electronic devices and electric vehicles (EVs). Despite their widespread use and associated advantages, LIBs still face significant challenges in terms of cycle stability, safety, and fast charging capabilities. These challenges mainly stem from the formation of the solid electrolyte interphase (SEI) layer on the graphite anode. The SEI is formed by the irreversible decomposition of electrolyte components at the anode / electrolyte interface and is a key component to maintain the electrochemical stability of the anode and prevent excessive electrolyte consumption. However, a suboptimal SEI layer can have a negative impact on the graphite anode. This is mainly due to two reasons. First, the SEI may not be able to fully cover the graphite due to poor compatibility at the electrolyte / electrode interface. Second, the components of the SEI may be unstable. Especially in the fast charging system, at high rates, the negative reaction between the electrolyte and the electrode intensifies, the polarization of the electrode end interface increases, and the heat generation of the battery is uneven. This series of problems brings greater challenges to the negative electrode SEI. The existing lithium-ion batteries have no specific rules for how to construct a stable, low-impedance and uniform SEI layer. There are large differences between different lithium-ion batteries. Therefore, how to construct a highly stable and low DCIR SEI film is an urgent problem to be solved. Summary of the invention

[0003] Aiming at the problem that the existing lithium ion batteries have insufficient rate performance, high temperature performance and low temperature performance, the present invention provides a lithium ion battery.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0005] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer containing a negative electrode active material and a negative electrode interface film formed on the surface of the negative electrode material layer, and the specific surface area of ​​the negative electrode material layer is 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm to 17μm, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, and the additive comprises a lithium salt type additive and a compound shown in structural formula 1;

[0006]

[0007] Wherein n is 0 or 1, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2;

[0008] The negative electrode surface is tested by an X-ray photoelectron spectrometer, and the ratio of the peak area Wa of the inorganic component with a binding energy of 680-685 eV to the peak area Wb of the organic component with a binding energy of 165-175 eV satisfies: 0.5≤Wa / Wb≤10.

[0009] Optionally, the lithium-ion battery meets the following conditions:

[0010] 0.8≤Wa / Wb≤8.

[0011] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by the structural formula 1 is 0.1% to 3%.

[0012] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the lithium salt additive is 0.01% to 2%.

[0013] Optionally, the lithium salt additive includes one or more of LiODFB (lithium difluorooxalatoborate) and LiODFP (lithium difluorooxalatophosphate).

[0014] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds:

[0015]

[0016]

[0017]

[0018] Optionally, the specific surface area of ​​the negative electrode material layer is 1.0 to 4 m 2 / g, and / or

[0019] The median particle size of the negative electrode material layer is 10 μm to 15 μm.

[0020] Optionally, the formation conditions of the lithium ion battery are:

[0021] The forming temperature is 40℃~50℃, and the forming pressure is 2~8kg / cm 2 , the charging current is 0.05C~0.12C, and the discharging current is 0.1C~0.3C.

[0022] Optionally, the additive further includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, borate compounds and nitrile compounds.

[0023] Optionally, the cyclic sulfate ester compound includes at least one of vinyl sulfate, 1,3,2-dioxathiacyclohexane-2,2-dioxide, and methyl vinyl sulfate; and / or

[0024] The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and 1,3-propene sultone; and / or

[0025] The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2:

[0026]

[0027] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or

[0028] The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3:

[0029]

[0030] In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; and / or

[0031] The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or

[0032] The nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0033] According to the lithium-ion battery provided by the present invention, the compound shown in structural formula 1 and the lithium salt type additive are added to the non-aqueous electrolyte. In the battery formation stage, the compound shown in structural formula 1 and the lithium salt type additive will decompose together on the surface of the negative electrode material layer to form a negative electrode interface film containing organic components and inorganic components mixed with each other. The inventors have found through a lot of research that by adjusting the ratio of the compound shown in structural formula 1 and the lithium salt type additive and controlling the specific surface area of ​​the negative electrode material layer to 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm~17μm, when the inorganic component Wa of the negative electrode interface film on the negative electrode surface and the organic component Wb of the negative electrode interface film meet the condition 0.5≤Wa / Wb≤10, the obtained lithium ion battery can simultaneously take into account better high-rate charge and discharge performance, high temperature performance and low temperature performance. It is speculated that under this condition, a thinner, denser and more stable negative electrode interface film can be formed, and the proportions of organic components and inorganic components in the negative electrode interface film are coordinated with each other, which can optimize the lithium ion interface transmission channel, improve the low-temperature performance and rate performance, and achieve the best high-temperature storage performance. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The embodiment of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer including a negative electrode material layer and a negative electrode interface film formed on the surface of the negative electrode material layer, wherein the specific surface area of ​​the negative electrode material layer is 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm to 17μm, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, and the additive comprises a lithium salt type additive and a compound shown in structural formula 1:

[0036]

[0037] Wherein n is 0 or 1, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2;

[0038] The negative electrode surface is tested by an X-ray photoelectron spectrometer, and the ratio of the peak area Wa of the inorganic component with a binding energy of 680-685 eV to the peak area Wb of the organic component with a binding energy of 165-175 eV satisfies: 0.5≤Wa / Wb≤10.

[0039] The migration rate of lithium ions at the negative electrode interface is the key factor determining low-temperature impedance. The speed of lithium ion migration at the negative electrode interface is determined by the negative electrode interface film. The formation path and composition of the negative electrode interface film are very complex. It is affected by many factors, such as the content of additives in the electrolyte, the particle size and specific surface area of ​​the negative electrode material layer, the battery cell preparation process parameters and battery formation conditions.

[0040] In the present invention, during the battery formation stage, the compound shown in structural formula 1 and the lithium salt additive will decompose together on the surface of the negative electrode material layer to form a negative electrode interface film containing organic components and inorganic components mixed with each other. The inventors have found through extensive research that by adjusting the ratio of the compound shown in structural formula 1 and the lithium salt additive and controlling the specific surface area of ​​the negative electrode material layer to be 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm~17μm, when the inorganic component Wa of the negative electrode interface film and the organic component Wb of the negative electrode interface film meet the condition 0.5≤Wa / Wb≤10, the obtained lithium ion battery can take into account both better high temperature performance and low temperature performance. It is speculated that under this condition, a thinner, denser and more stable negative electrode interface film can be formed, and the proportions of the organic component and the inorganic component in the negative electrode interface film are coordinated with each other, which can optimize the lithium ion interface transmission channel, improve the low temperature performance and rate performance, and at the same time achieve the best high temperature storage performance.

[0041] In some embodiments, the lithium-ion battery meets the following conditions:

[0042] 0.8≤Wa / Wb≤8.

[0043] When the inorganic component Wa of the negative electrode interface film and the organic component Wb of the negative electrode interface film further meet the above conditions, it is beneficial to further improve the rate charge and discharge performance, high temperature performance and low temperature performance of the lithium-ion battery.

[0044] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by Structural Formula 1 is 0.1% to 3%.

[0045] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by the structural formula 1 is 0.1% to 2%.

[0046] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the compound represented by structural formula 1 can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.7% or 3%.

[0047] By adding the compound shown in structural formula 1 with S element as the central atom, due to its excellent film-forming performance, it is superior to the film-forming of general solvents and additives, and can form a stable negative electrode interface film at the negative electrode. Through XPS testing, it is found that the compound shown in structural formula 1 promotes the increase of sulfur-containing organic film components in the composition of the negative electrode interface film. The increase of organic components in the interface film is conducive to the improvement of electrochemical stability, which is conducive to inhibiting the side reaction between the non-aqueous electrolyte and the negative electrode. At the same time, the formed lithium sulfate has advantages over alkoxy lithium in the transmission of lithium ions. If the content of the compound shown in structural formula 1 in the non-aqueous electrolyte is too low, the film-forming performance of the negative electrode interface film will be limited; if the content of the compound shown in structural formula 1 in the non-aqueous electrolyte is too high, the negative electrode interface film will be too thick. Based on the characteristics of the organic film, the overall impedance will be degraded, which is not conducive to the conduction of lithium ions.

[0048] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the lithium salt additive is 0.01% to 2%.

[0049] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the lithium salt additive is 0.01% to 1%.

[0050] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the lithium salt additive can be 0.01%, 0.03%, 0.05%, 0.06%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%.

[0051] The kinetics of lithium salt type additives in the negative electrode film formation are similar to those of the compounds shown in Structural Formula 1. After the lithium salt type additives are formed in the negative electrode, the inorganic components of the negative electrode interface film will increase. The increase in inorganic components significantly improves the thermal stability of the interface film and is beneficial to the conduction of lithium ions. The film formation interval of the lithium salt type additive will be staggered with that of the compound shown in Structural Formula 1, which also makes the inorganic and organic matter in the negative electrode interface film staggered and stacked on the negative electrode, and will not cause the organic and inorganic matter to be stacked separately. If the content of the lithium salt type additive in the non-aqueous electrolyte is too low, it will be difficult to improve the thermal stability of the negative electrode interface film; if the content of the lithium salt type additive in the non-aqueous electrolyte is too high, it will be detrimental to the kinetic stability of the interface film, and the gas production and impedance will deteriorate in the later stage of storage.

[0052] It should be noted that in the non-aqueous electrolyte, the mass percentage content of the compound shown in Structural Formula 1 and the mass percentage content of the lithium salt-type additive will affect the content of the decomposition products of the compound shown in Structural Formula 1 and the decomposition products of the lithium salt-type additive in the negative electrode interface film, but are not the only influencing factors. For example, since the compound shown in Structural Formula 1 and the lithium salt-type additive have different decomposition potentials, changes in the formation conditions will also lead to differences in the decomposition of the compound shown in Structural Formula 1 and the lithium salt-type additive, and then the ratio of organic components and inorganic components in the negative electrode interface film can be regulated by the formation conditions; for example, the morphology of the negative electrode active material affects the formation of the negative electrode interface film. Under different specific surface areas of the negative electrode material layer and particle sizes of the negative electrode material layer, the ratio of organic components and inorganic components in the obtained negative electrode interface film is different.

[0053] In some embodiments, the lithium salt additive includes one or more of LiODFB and LiODFP.

[0054] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds:

[0055]

[0056]

[0057]

[0058] In a specific embodiment, the specific surface area of ​​the negative electrode material layer can be 0.5 m 2 / g, 0.7m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m2 / g, 1.5m 2 / g, 1.8m 2 / g, 2m 2 / g, 2.2m 2 / g, 2.5m 2 / g, 2.8m 2 / g, 3m 2 / g, 3.2m 2 / g, 3.5m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.2m 2 / g, 4.5m 2 / g, 4.8m 2 / g or 5m 2 / g.

[0059] In a preferred embodiment, the specific surface area of ​​the negative electrode material layer is 1.0 to 4 m 2 / g.

[0060] The testing method for the specific surface area of ​​the negative electrode material layer is:

[0061] (1) Remove the negative electrode sheet from the battery, soak and clean it with DMC (dimethyl carbonate), place it in a glove box and vacuum dry it for 24 hours, scrape the negative electrode material layer from the negative electrode current collector into powder, then add a small amount of DMC to the powder and disperse it using an ultrasonic device. After drying, take 30 to 500 mg (depending on the specific surface area of ​​the sample) and put it into a sample tube.

[0062] (2) Place the sample tube in a degassing station, heat the sample, and perform vacuum degassing to remove the gas adsorbed on the surface of the material.

[0063] (3) After degassing, measure the mass of the sample.

[0064] (4) Then, a BET analyzer (model: JW-BK112, manufacturer: Jingwei Gaobo) was used to perform adsorption and desorption tests on the samples;

[0065] (5) The specific surface area is calculated from the adsorption isotherm by computer processing the data.

[0066] In a specific embodiment, the median particle size of the negative electrode material layer may be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or 17 μm.

[0067] In a preferred embodiment, the median particle size of the negative electrode material layer is 10 μm to 15 μm.

[0068] The testing method for the median particle size of the negative electrode material layer is as follows: the negative electrode sheet is disassembled from the battery, the electrode sheet is soaked and cleaned with DMC (dimethyl carbonate), and vacuum-dried in a glove box for 24 hours, the negative electrode material layer is scraped off the negative electrode current collector into powder, and then a small amount of DMC is added to the powder and dispersed using an ultrasonic device. After drying, the Dv50 particle size (median particle size) of the negative electrode is tested using a particle size analyzer (model: Mastersizer 2000).

[0069] The specific surface area of ​​the negative electrode material layer and the median particle size of the negative electrode material layer will affect the film-forming quality of the negative electrode interface film on the surface of the negative electrode material layer and the ratio of organic components to inorganic components. Specifically, the specific surface area of ​​the negative electrode material layer and the median particle size of the negative electrode material layer affect the contact area between the non-aqueous electrolyte and the negative electrode material layer, and under the same formation conditions, affect the consumption rate of the lithium salt additive and the compound shown in structural formula 1 in the non-aqueous electrolyte, thereby controlling the formation of the negative electrode interface film with different ratios of organic components and inorganic components.

[0070] In some embodiments, the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.

[0071] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.

[0072] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.

[0073] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.

[0074] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.

[0075] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.

[0076] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0077] In some embodiments, the formation conditions of the lithium ion battery are:

[0078] The forming temperature is 40℃~50℃, and the forming pressure is 2~8kg / cm 2 , the charging current is 0.05C~0.12C, and the discharging current is 0.1C~0.3C.

[0079] In some embodiments, the additive further comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound, and a nitrile compound.

[0080] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the content of the additive is 0.01% to 10%.

[0081] In some embodiments, the cyclic sulfate ester compound includes at least one of vinyl sulfate, 1,3,2-dioxathiacyclohexane-2,2-dioxide, and methyl vinyl sulfate.

[0082] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone.

[0083] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, or a compound shown in Structural Formula 2:

[0084]

[0085] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.

[0086] In some embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in formula 3:

[0087]

[0088] In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group.

[0089] In a preferred embodiment, the phosphate compound shown in the structural formula 3 may be at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0090] In some embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.

[0091] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.

[0092] In other embodiments, the additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.

[0093] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the additives in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1% to 2%. Specifically, the content of any one of the optional substances in the additives can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.

[0094] In some embodiments, the additive includes fluoroethylene carbonate, and based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the fluoroethylene carbonate is 0.01% to 30%.

[0095] In some embodiments, the lithium salt includes LiPF6, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.

[0096] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L or 2.5mol / L.

[0097] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.

[0098] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, or 90%.

[0099] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.

[0100] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. The amount of the ether compound added is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more in the non-aqueous solvent volume ratio of 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.

[0101] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.

[0102] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate can be specifically but not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonate can be specifically but not limited to at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). There is no special restriction on the content of the cyclic carbonate, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the reduction in conductivity due to the reduction in the dielectric constant of the non-aqueous electrolyte can be avoided, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually less than 90% by volume, preferably less than 85% by volume, and more preferably less than 80% by volume. By setting this range, the oxidation / reduction tolerance of the nonaqueous electrolyte can be improved, thereby helping to improve the stability during high temperature storage. The content of the linear carbonate is not particularly limited, and relative to the total amount of solvent of the nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of the linear carbonate in the above-mentioned range, it is easy to make the viscosity of the nonaqueous electrolyte reach an appropriate range, suppress the reduction of ionic conductivity, and then help to make the output characteristics of the nonaqueous electrolyte battery reach a good range. When two or more linear carbonates are used in combination, the total amount of the linear carbonate is made to meet the above-mentioned range.

[0103] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.

[0104] Carboxylate solvents include cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.

[0105] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent in the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can meet the above range. When the amount of sulfone solvent added is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.

[0106] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonate and linear carbonate.

[0107] In some embodiments, the positive electrode material layer includes a positive electrode active material, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.

[0108] In some embodiments, the molar ratio of Ni element in the positive electrode active material is ≥0.3.

[0109] In a preferred embodiment, the molar ratio of Ni element in the positive electrode active material is 0.3-0.7.

[0110] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.

[0111] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.

[0112] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0113] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.

[0114] In some embodiments, the lithium-ion battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.

[0115] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.

[0116] In some embodiments, the charging cut-off voltage of the lithium-ion battery is ≥4.35V.

[0117] In a preferred embodiment, the charging cut-off voltage of the lithium ion battery is 4.35 V to 4.5 V. The present invention is further described below by way of examples.

[0118] Table 1

[0119]

[0120]

[0121]

[0122] Example 1

[0123] This example is used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, which includes the following steps:

[0124] 1) Preparation of electrolyte

[0125] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and then the additives shown in Table 1 are added based on the total mass of the electrolyte.

[0126] 2) Preparation of positive electrode

[0127] The positive electrode active material LiNi was mixed in a mass ratio of 93:4:3 0.6 Co 0.2 Mn 0.2 O2, conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive electrode plate with a thickness of 120-150μm.

[0128] 3) Preparation of negative electrode plate

[0129] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled and vacuum dried, and welded with a nickel lead wire using an ultrasonic welder to obtain a negative electrode plate. The thickness of the plate was 120-150 μm. The median particle size and specific surface area of ​​the negative electrode material layer are shown in Table 1.

[0130] 4) Preparation of battery cells

[0131] A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.

[0132] 5) Battery filling and formation

[0133] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 24 hours. Then the first charge formation was carried out, and the formation conditions were: formation temperature of 45°C, formation pressure of 4kg / cm 2 , the charging current is 0.1C and the discharging current is 0.2C.

[0134] Embodiments 2 to 45

[0135] Examples 2 to 45 are used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, and include most of the operation steps in Example 1, except that:

[0136] The types of positive electrode active materials, additives in the non-aqueous electrolyte and their addition amounts, the median particle size of the negative electrode material layer, and the specific surface area of ​​the negative electrode material layer are shown in Table 1;

[0137] In Example 39, the positive electrode active material is LiNi 0.5 Co 0.25 Mn 0.3 O2, the positive electrode active material in Example 40 is LiNi 0.7 Co 0.1 Mn 0.2 O2, the positive electrode active material in Example 41 is LiNi 0.6 Co 0.2 Al 0.2 O2, the positive electrode active material in Example 42 is LiNi 0.6 Co 0.2 Mn 0.05 Al 0.05 O2.

[0138] Comparative Examples 1 to 12

[0139] Comparative Examples 1 to 12 are used to compare and illustrate the method for preparing a lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that:

[0140] The additives in the non-aqueous electrolyte and their addition amounts, the median particle size of the negative electrode material layer, and the specific surface area of ​​the negative electrode material layer are shown in Table 1.

[0141] Performance Testing

[0142] The lithium-ion battery prepared above was subjected to the following performance tests:

[0143] 1. X-ray Photoelectron Spectrometer (XPS) Test

[0144] The lithium-ion battery was discharged to 2.5V at a current of 0.1C, and the lithium-ion battery was disassembled in a glove box filled with argon to obtain the negative electrode sheet. The obtained negative electrode sheet was cut into a test sample of 5mm×5mm size, and soaked and cleaned with a low-boiling dimethyl carbonate (DMC) solvent for 30 seconds. After being completely dried, it was pasted on the sample stage of XPS, so that the surface of the negative electrode material layer facing away from the current collector was facing upward, and the measurement was performed without exposure to the atmosphere. The specific test conditions and steps are as follows: using an Ar ion gun to etch at a speed of 10nm / min, the etching power is 1kV, and the data when the etching time is 0s is selected for data processing. The peak area of ​​the inorganic component at the position of the binding energy of 680~685eV is taken, and the peak area of ​​the organic component at the position of the binding energy of 165~175eV is taken. The background is subtracted and the peak value is synthesized, and the ratio of the peak area Wa of the inorganic component in the negative electrode interface film to the peak area Wb of the organic component is calculated, and the test results are filled in Table 1.

[0145] 2. High temperature cycle performance test

[0146] The formed lithium-ion battery was placed in an oven at a constant temperature of 45°C, charged at a constant current of 1C to the cut-off voltage, then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a constant current of 1C to 3.0V. This cycle was repeated, and the first discharge capacity and the last discharge capacity were recorded.

[0147] The capacity retention rate of high temperature cycle is calculated as follows:

[0148] Capacity retention rate (%) = last discharge capacity / first discharge capacity×100%.

[0149] 3. Rate Cycle Performance Test

[0150] The formed lithium-ion battery was placed in an oven at a constant temperature of 25°C, charged to 80% SOC at a constant current of 4C, then charged to the cut-off voltage at a constant current and voltage of 1C, with a cut-off current of 0.05C, and then discharged to 3.0V at a constant current of 1C. This cycle was repeated, and the first discharge capacity and the last discharge capacity were recorded.

[0151] The capacity retention rate of rate cycling is calculated as follows:

[0152] Capacity retention rate (%) = last discharge capacity / first discharge capacity×100%.

[0153] 4. High temperature storage performance test

[0154] The formed lithium-ion battery was charged to the cut-off voltage at room temperature using a constant current and constant voltage of 0.5C, and the initial discharge capacity and initial battery thickness of the battery were measured. After being stored in a 60°C environment for 30 days, the battery was discharged to 3V at 1C, and the battery retention capacity and recovery capacity as well as the battery thickness after storage were measured. The calculation formula is as follows:

[0155] Battery capacity retention rate (%) = retention capacity / initial capacity × 100%;

[0156] Battery capacity recovery rate (%) = recovery capacity / initial capacity × 100%;

[0157] Thickness expansion ratio (%) = (battery thickness after storage - initial battery thickness) / initial battery thickness × 100%.

[0158] 5. Low temperature performance test

[0159] At 25°C, the formed battery was charged to the cut-off voltage with 1C constant current and constant voltage, and then discharged to 3.0V with 1C constant current, and the discharge capacity was recorded. Then, the battery was charged to the cut-off voltage with 1C constant current and constant voltage, placed in a -20°C environment for 12 hours, and then discharged to 3.0V with 0.5C constant current, and the discharge capacity was recorded.

[0160] Low-temperature discharge efficiency value at -20°C (%) = 0.5C discharge capacity (-20°C) / 1C discharge capacity (25°C) × 100%.

[0161] (1) The test results obtained in Examples 1 to 30 and Comparative Examples 1 to 12 are entered in Table 2.

[0162] Table 2

[0163]

[0164]

[0165]

[0166] It can be seen from the test results of Examples 1 to 30 and Comparative Examples 1 to 12 that in the battery system to which the compound represented by Structural Formula 1 and the lithium salt additive are added, the specific surface area of ​​the negative electrode material layer is controlled to be 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm~17μm, when the inorganic component Wa of the negative electrode interface film and the organic component Wb of the negative electrode interface film meet the condition 0.5≤Wa / Wb≤10, the obtained lithium ion battery simultaneously takes into account better high-rate charge and discharge performance, high temperature performance and low temperature performance. It is speculated that under this condition, a thinner, denser and more stable negative electrode interface film can be formed, and the proportions of the organic component and the inorganic component in the negative electrode interface film are coordinated with each other, which can optimize the lithium ion interface transmission channel, improve the low-temperature performance and rate performance, and achieve the best high-temperature storage performance.

[0167] It can be seen from the test results of Examples 1 to 30 that when the inorganic component Wa of the negative electrode interface film and the organic component Wb of the negative electrode interface film further satisfy the condition 0.8≤Wa / Wb≤8, the high temperature stability and ion conductivity of the solid electrolyte membrane on the surface of the obtained negative electrode material layer are further improved, and the high temperature performance, low temperature performance and rate performance of the battery all reach a relatively high level.

[0168] It can be seen from the test results of Comparative Examples 5 to 12 that when the Wa / Wb value does not satisfy the limitation of 0.5≤Wa / Wb≤10, even if the compound shown in Structural Formula 1 and the lithium salt type additive are added and the addition amount of the compound shown in Structural Formula 1 and the lithium salt type additive meets the range limitation, the obtained lithium ion battery still cannot take into account both high and low temperature performance, indicating that the adjustment of the specific surface area of ​​the negative electrode material layer and the median particle size of the negative electrode material layer will also affect the ratio of organic components and inorganic components in the negative electrode interface film. When and only when multiple influencing factors reach a better balance state, the high temperature stability and ion conductivity of the negative electrode interface film at the interface of the negative electrode material layer can be significantly improved.

[0169] It can be seen from the test results of Comparative Examples 1 to 4 that when the compound shown in Structural Formula 1 and the lithium salt-type additive are not used as electrolyte additives at the same time, even if the Wa / Wb value is adjusted to meet the limitation of 0.5≤Wa / Wb≤10, the high temperature performance, low temperature performance and rate performance of the lithium-ion battery will be deteriorated, indicating that the conditional limitations of the present battery system are only applicable to the electrolyte system to which the compound shown in Structural Formula 1 and the lithium salt-type additive are added, and its performance improvement is directly related to the compound shown in Structural Formula 1 and the lithium salt-type additive.

[0170] (2) The test results obtained in Examples 1 and 31 to 38 are entered in Table 3.

[0171] Table 3

[0172]

[0173] It can be seen from the test results of Examples 1 and 31 to 38 that when different compounds represented by structural formula 1 and lithium salt-type additives are used, under the premise of satisfying the condition 0.5≤Wa / Wb≤10, lithium-ion batteries with excellent high-temperature storage performance, high-rate charge and discharge performance and low-temperature discharge capacity retention rate can be obtained, indicating that the battery system provided by the present invention is suitable for different compounds represented by structural formula 1 and lithium salt-type additives.

[0174] (3) The test results obtained in Examples 1, 39 to 42 are entered in Table 4.

[0175] Table 4

[0176]

[0177] It can be seen from the test results of Examples 1 and 39 to 42 that in the battery system provided by the present invention, when different positive electrode active materials are used, the various performances of the lithium-ion battery will be affected to a certain extent, but in general, the lithium-ion battery that meets the condition 0.5≤Wa / Wb≤10 maintains a relatively good level in high temperature performance, low temperature performance and rate performance.

[0178] (4) The test results obtained in Examples 1 and 43 to 45 are entered in Table 5.

[0179] Table 5

[0180]

[0181] It can be seen from the test results of Examples 1 and 43 to 45 that when DTD (vinyl sulfate), PS (1,3-propane sultone) or FEC (fluoroethylene carbonate) is used in combination with the compound shown in Structural Formula 1 and a lithium salt-type additive, the high and low temperature performance of the lithium-ion battery is improved to a certain extent. It is speculated that this is because the mechanism of improving battery performance by other additives is somewhat different from that of the compound shown in Structural Formula 1 and the lithium salt-type additive. The three have a complementary effect on film formation, thereby improving the stability of the interface film on the surface of the negative electrode material layer, and can further improve the cycle stability and high and low temperature performance of the battery.

[0182] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer containing a negative electrode active material and a negative electrode interface film formed on the surface of the negative electrode material layer, and the specific surface area of ​​the negative electrode material layer is 0.5 to 5 m 2 / g, the median particle size of the negative electrode material layer is 8μm to 17μm, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, and the additive comprises a lithium salt additive and a compound shown in structural formula 1: Wherein n is 0 or 1, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2; The negative electrode surface is tested by an X-ray photoelectron spectrometer, and the ratio of the peak area Wa of the inorganic component with a binding energy of 680-685 eV to the peak area Wb of the organic component with a binding energy of 165-175 eV satisfies: 0.5≤Wa / Wb≤10.

2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery meets the following conditions: 0.8≤Wa / Wb≤8.

3. The lithium-ion battery according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by the structural formula 1 is 0.1% to 3%.

4. The lithium-ion battery according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the lithium salt additive is 0.01% to 2%.

5. The lithium ion battery according to claim 1 or 4, characterized in that: The lithium salt additive includes one or more of LiODFB and LiODFP.

6. The lithium-ion battery according to claim 1, characterized in that The compound represented by the structural formula 1 includes one or more of the following compounds:

7. The lithium-ion battery according to claim 1, characterized in that: The specific surface area of ​​the negative electrode material layer is 1.0 to 4 m 2 / g, and / or The median particle size of the negative electrode material layer is 10 μm to 15 μm.

8. The lithium-ion battery according to claim 1, characterized in that The formation conditions of the lithium ion battery are: The forming temperature is 40℃~50℃, and the forming pressure is 2~8kg / cm 2 , the charging current is 0.05C~0.12C, and the discharging current is 0.1C~0.3C.

9. The lithium-ion battery according to claim 1, characterized in that: The additive further includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, borate compounds and nitrile compounds.

10. The lithium ion battery according to claim 9, characterized in that: The cyclic sulfate ester compound includes at least one of vinyl sulfate, 1,3,2-dioxathiacyclohexane-2,2-dioxide, and methyl vinyl sulfate; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and 1,3-propene sultone; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2: In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3: In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; and / or The borate compound comprises at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or The nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

Citation Information

Patent Citations

  • Lithium secondary battery

    CN115036572A

  • Lithium ion battery

    CN115064770A

  • Lithium ion battery

    CN115498268A

  • Lithium ion battery

    CN117080557A

  • Lithium ion battery

    CN118315680A

Cited By

  • Lithium-ion battery

    WO2026016715A1

  • Electrolyte, battery, and electric device

    WO2026138763A1

  • Battery and electric device

    WO2026208459A1